Faktor risiko kejadian hepatitis b pada ibu hamil di Kabupaten Bombana tahun 2024 - Basir, Andi Radya Tulmuayada; Sabilu, Yusuf; Karimuna, Siti Rabbani (PT WIM Solusi Prima, 2024)
The impact of hepatitis B Transmission from infected mothers to children is a significant contributor to the high prevalence of hepatitis B in Indonesia. This study seeks to analyze the risk factors associated with pregnant women who have Hepatitis B in Bombana Regency in 2023. The research utilizes a quantitative case-control study design with a retrospective approach.The number of samples in this study involved 33 pregnant women positive for hepatitis b, and 33 negative people for hepatitis b using the total sampling technique of the results of the study there were differences in knowledge with a p-value of 0.003 (p 0.05), contact history with a p-value of 0.001 (p 0.05), the role of health workers with a p-value of 0.004 (p 0.05), and the environment with a p-value of 0.026 (p 0.05) with Hepatitis B Patients in Pregnant Women in the District Bombana in 2024conclusion there are differences between knowledge, contact history, the role of health workers, and the environment with hepatitis B patients in pregnant women in Bombana District in 2024. Angka prevalensi hepatitis B pada anak di Negara Indonesia cenderung meningkat akibat adanya riwayat hepatitis B pada ibu. Adapun tujuan dari terlaksanaya penelitian ini yaitu mengevaluasi faktor risiko ibu hamil yang menderita hepatitis B periode 2023 di Kabupaten Bombana. Jenis Penelitian ini yaitu penelitian kuantitatif case control study dan mengimplementasikan metode pendekatan retrospektif, Jumlah sampel ynag ditetapkan sejumlah 33 orang ibu hamil positif hepatitis b, dan 33 orang negatif hepatitis b dengan menggunakan teknik total sampling. Hasil Penelitian terdapat perbedaan pengetahuan dengan nilai p-value sebesar 0,003 (p 0,05), riwayat kontak dengan nilai p-value sebesar 0,001 (p 0,05), peran tenaga kesehatan dengan nilai p-value sebesar 0,004 (p 0,05), dan lingkungan dengan nilai p-value sebesar 0,026 (p 0,05) Dengan Penderita Hepatitis B Pada Ibu Hamil di Kabupaten Bombana Tahun 2024. Kesimpulan terdapat perbedaan antara pengetahuan, riwayat kontak, peran tenaga kesehatan, dan lingkungan Dengan Penderita Hepatitis B Pada Ibu Hamil di Kabupaten Bombana Tahun 2024.